PENGARUH STRATEGI PEMASARAN TERHADAP JUMLAH KONSUMEN PADA RUMAH MAKAN PRINGSEWU KECAMATAN SUMPIUH - Bayu Sudrajat; Aji Fany Permana; Anita Oktariyana (EL MUDHORIB : Jurnal Kajian Ekonomi dan Perbankan Syariah, 2021)
Currently the existence of restaurants is very easy to find, one of which is the restaurant "Pringsewu" which is located in the Sumpiuh sub-district, Banyumas Regency. To maintain, maintain the existence and develop its business, it takes the right marketing strategy in the restaurant business. The statement of the problem in this study is how the influence of marketing strategy on the number of consumers. The purpose of this study was to analyze the effect of marketing strategy with marketing mix indicators on the number of consumers at Pringsewu Sumpiuh restaurant. This research is a field research using a quantitative approach. Respondents who were used as samples were 100 consumers. Analysis of the data using the validity test method, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the Pringsewu Sumpiuh restaurant implements a marketing strategy using 4p (product, price, place, and promotion) to increase the number of consumers. In addition, the results of this study have a regression equation Y = 8.584 + 0.575X1 + 0.232X2 + 0.678X3 + 0.006X4. Furthermore, the calculation of the coefficient of determination (R2) is 0.910 or 91.0%. This shows that 91.0% of the dependent variable (number of consumers) is influenced by product, price, place and promotion. The f test results show that product, price, place and promotion together have a significant influence on the number of consumers. Based on the results of the t test analysis shows that the promotion has a significant influence on the number of consumers.